A climate-sensitive forest model for assessing impacts of forest management in Europe. (May 2019) - Härkönen, S.; Neumann, M.; Mues, V.; Berninger, F.; Bronisz, K.; Cardellini, G.; Chirici, G.; Hasenauer, H.; Koehl, M.; Lang, M.; Merganicova, K.; Mohren, F.; et al.
Abstract: FORMIT-M is a widely applicable, open-access, simple and flexible, climate-sensitive forest management simulator requiring only standard forest inventory data as input. It combines a process-based carbon balance approach with a strong inventory-based empirical component. The model has been linked to the global forest sector model EFI-GTM to secure consistency between timber cutting and demand, although prescribed harvest scenarios can also be used. Here we introduce the structure of the model and demonstrate its use with example simulations until the end of the 21st century in Europe, comparing different management scenarios in different regions under climate change. The model was consistent with country-level statistics of growing stock volumes (R 2 = 0.938) and its projections of climate impact on growth agreed with other studies. The management changes had a greater impact on growing stocks, harvest potential and carbon balance than projected climate change, at least in the absence of increased disturbance rates. Highlights: FORMIT-M is a simple-to-use open-access forest management simulator for Europe. It combines process-based and data-based components. It uses standard forest inventory data and climate scenarios as input. Conventional and alternative management scenarios follow practices in European regions. Management had a greater impact on carbon stocks and harvest potential than climate change.